2019
DOI: 10.1071/an17255
|View full text |Cite
|
Sign up to set email alerts
|

Do triclabendazole medicated molasses blocks have a role in control of Fasciola gigantica in smallholder cattle production in Lao PDR?

Abstract: Smallholder cattle production in many developing tropical countries including Laos is compromised by widespread endoparasitism, with limited farmer knowledge of parasites and facilities for administration of therapeutics. We report a pilot study examining the potential for triclabendazole provided in medicated molasses blocks offered to control Fasciola gigantica in smallholder cattle production. This study involved 241 cattle allocated into three groups: (1) triclabendazole (as Fasinex®, Novartis Animal Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(44 citation statements)
references
References 16 publications
5
39
0
Order By: Relevance
“…The trial suggests an advantage of up to a 31% increase in daily milk production, albeit from a very low base milk yield level, as a result of block supplementation for several months. This provides additional evidence of the efficacy of molasses block technology in successfully enhancing productivity through supplementation of the generally inefficient large ruminant smallholder production system, as demonstrated previously in dairy buffalo in other countries [12] and recently in beef animals in Laos [13,14,15]. Previous trials with UMNBsupplemented buffaloes in South Asia [12] also showed increased milk yield and higher milk fat values than did their un-supplemented counterparts, calculated as an average increase of 8% milk yield and 0.5 percentage unit milk fat [21].…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…The trial suggests an advantage of up to a 31% increase in daily milk production, albeit from a very low base milk yield level, as a result of block supplementation for several months. This provides additional evidence of the efficacy of molasses block technology in successfully enhancing productivity through supplementation of the generally inefficient large ruminant smallholder production system, as demonstrated previously in dairy buffalo in other countries [12] and recently in beef animals in Laos [13,14,15]. Previous trials with UMNBsupplemented buffaloes in South Asia [12] also showed increased milk yield and higher milk fat values than did their un-supplemented counterparts, calculated as an average increase of 8% milk yield and 0.5 percentage unit milk fat [21].…”
Section: Discussionsupporting
confidence: 67%
“…This research trial aimed to further examine the recent research findings in Laos conducted with beef animals, that showed that significant improvements in ADG could accrue from supplementation with NMB and UNMB8 [13,14,15], with young calves having the highest ADG (251-265 g/day) presumably due to their access to increased milk from their dams [15]. The preliminary findings in this trial in a buffalo dairy, following supplementing of the forage-based diet of lactating buffalo with ad libitum access to 'Cow-Calf' UMNB10, are indicative of considerable increases in daily milk production, without a loss in BCS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, these results should be interpreted with caution as LWC responses and MLB intake between individual animals could largely differ, as we show in a companion paper (unpublished data) [17]. In addition to the nutritional benefits of supplementing MLB, ionophores included in the blocks (Lasalocid sodium) could have been effective to control common diseases of young cattle, such as coccidiosis, while improving feed efficiency [18,19]. The availability of minerals from MLB could also influence LWC of weaners as minerals are usually deficient in most forages in comparison to the high requirements of young growing cattle [20].…”
Section: Discussionmentioning
confidence: 97%